2013
DOI: 10.1007/s00381-013-2110-z
|View full text |Cite
|
Sign up to set email alerts
|

Tectal plate gliomas: a review

Abstract: MRI studies reveal a characteristic well-circumscribed, isodense or hypodense mass on T1-weighted images, with hyperdensity on T2 imaging. Yet current radiological methods insufficiently distinguish tectal plate gliomas from brainstem tumors or gliomas in the neighboring structures, and a definitive diagnosis requires biopsy and histopathological analysis. Management is planned according to the degree of associated signs and symptoms, and may range from diligent observation and periodic screening for advancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…A review of the literature indicated that 80% of the tumors are low-grade gliomas [2,3,4] that typically appear on MRIs as hypo- or isointense masses on T1, hyperintense on T2, and rarely enhance after contrast injection [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature indicated that 80% of the tumors are low-grade gliomas [2,3,4] that typically appear on MRIs as hypo- or isointense masses on T1, hyperintense on T2, and rarely enhance after contrast injection [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Tectal glioma is a glioma that arises in the midbrain and is rare in adults. 4 It is a benign tumor that occurs mainly in children. A high seizure prevalence rate of 12.1% (8 of 66) has been reported; however, 50% were seizures not related to the tumor, such as febrile seizure, meningitis, and postoperative sequelae, and tectal glioma was discovered inciden-tally during the seizure evaluation in 25% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management involving CSF diversion and no surgical biopsy or resection of tectal lesions has been the favoured approach when such lesions demonstrate characteristic imaging findings of low-grade tumor, indolent growth, and the absence of progressive neurological deficit. 5 While focal tectal and tegmental midbrain lesions may have a benign clinical course, there is still a risk for tumor growth or transformation to higher grade necessitating continued surveillance after surgical intervention to relieve obstructive hydrocephalus. In a series of seven patients under the age of 25, increase in tumor size was observed in six patients and the magnitude of increase in size ranged from 1.6 to 3.8 times the original size.…”
Section: Discussionmentioning
confidence: 99%
“…The most common application of ETV has been in the setting of obstructive hydrocephalus to provide for a physiologic correction of hydrocephalus 2 potentially avoiding the complications of ventriculoperitoneal shunting such as recurrent for management of these tumors has emerged in the literature. 4,5 In the present study we evaluate the role of ETV in the management of obstructive hydrocephalus in patients with a clinical-radiologic diagnosis of tectal glioma. By reviewing our experience in this patient population we sought to ascertain the degree of symptom improvement with ETV and the risk of treatment failure as defined by the need for ventriculoperitoneal shunting.…”
mentioning
confidence: 99%